DIVORCE STATEMENT MODEL IN RELIGIOUS COURTS - Rosalina, Maria; Elyani, Elyani; Saragih, Noviyanti (NOMOI Law Review, 2025)
For Muslims , one of the reason break up bond marriage is existence decision from Religious Court based on lawsuit filed by an interested party . Lawsuit This can in the form of application divorce vow submitted by the husband as applicant , or lawsuit divorce filed by wife as plaintiff . After application the vow of divorce is terminated and has force law Still , the husband ( applicant) is obliged to pronounce vow of divorce in front of hearing Religious Court . In practice , the implementation this vow of divorce own several different models caused by various the problems that arise . This is what drives writer For examining the divorce vow model in the Religious Court and consequence law if husband No pronounce the divorce . Research This aiming For identify implementation models divorce oath in Religious Court and analyze consequence law If vow of divorce no spoken . Research This use method study law normative , with approach analysis to norm law positive in effect as well as using secondary data . For completing secondary data , done interview with practitioner law such as judges, notaries , and advocates . The results of the study show that there is various models of divorce vows in the Religious Court , and if husband ( applicant ) does not pronounce talaq in term the specified time , then right husband For pronounce the divorce fall and bond marriage still valid . In conclusion , there is various implementation models the oath of divorce in the Religious Court, which is influenced by problems between the parties .